Implementasi Metode Simple Additive Weighting (SAW) Pada Sistem Pendukung Keputusan Pemilihan Dosen Berprestasi - Rajagukguk, Denni M; Limbong, Riswan (MEANS (Media Informasi Analisa dan Sistem), 2017)
Outstanding lecturers are lecturers who in the last three years have had very useful and proud achievements in universities of origin, and are recognized on a national or international scale. The problem in choosing an outstanding lecturer at STMIK Budi Darma was that the management did not clearly understand the terms and procedures for the requirements to participate in the selection of outstanding lecturers at the Kopertis level and even at the national level, even though there were many lecturers who wanted to follow in STMIK Budi Darma. In the absence of a system to handle, almost all lecturers cannot and do not understand what must be done in implementing the higher education tridharma that supports the selection of Lecturers with Achievement. So that the outstanding lecturer selection service was built using computer tools in the form of applications by applying the Simple Additive Weighting (SAW) method as one of the Decision Support System (DSS) methods. The output of this study is a system application for supporting lecturer selection decisions, and will produce scientific papers in the form of publication journals in non-accredited national journals, so that university leaders and lecturers can process data and obtain fast, accurate and accurate information